Ontologi dan Epistmologi Proses Dialektika Wahyu (Akulturasi dan Negosiasi) dimensi Teosentris dan Antroposentris - Rahman, Fathur; Sari, Aminah Rahma (Maliki Interdisciplinary Journal, 2025)
This study examines the ontological and epistemological dimensions in the dialectical process of revelation, focusing on the dynamics of acculturation and negotiation between theocentric and anthropocentric aspects. This research reveals that ontologically, revelation has dual characteristics that unite transcendent and immanent dimensions through a complex dialectical process. Epistemologically, understanding revelation involves integrating divine knowledge methods and human rationality. Through in-depth analysis, this study demonstrates that the acculturation process occurs when revelatory messages interact with human knowledge systems and culture, while negotiation takes place in an effort to find common ground between the ideality of revelation and life's reality. The research results indicate that this dialectic produces a dynamic and contextual understanding of revelation while maintaining its fundamental substance. This study contributes to the development of a theoretical framework for understanding the complex relationship between revelation, interpretation, and its implementation in contemporary contexts, while highlighting the importance of an integrative approach in revelation studies that combines theological and anthropological perspectives.